Factors influencing attendance at structured education for Type 1 diabetes in south London. Issue 6 (9th March 2017) - Harris, S. M.; Shah, P.; Mulnier, H.; Healey, A.; Thomas, S. M.; Amiel, S. A.; Hopkins, D.
Abstract: Aim: To investigate the factors influencing uptake of structured education for people with Type 1 diabetes in our local population in order to understand why such uptake is low. Methods: We conducted a cross‐sectional database study of adults with Type 1 diabetes in two south London boroughs, analysed according to Dose Adjustment For Normal Eating (DAFNE) attendance or non‐attendance. Demographics, glycaemic control and service use, with subset analysis by ethnicity, were compared using univariate analysis. An exploratory regression model was used to identify influencing factors. Results: The analysis showed that 73% of adults had not attended the DAFNE programme. For non‐attenders vs attenders, male gender (59 vs 48%; P = 0.002), older age (39 vs 35 years; P < 0.001), non‐white ethnicity (30 vs 20%; P = 0.001) and coming from an area of social deprivation (index of multiple deprivation score 31 vs 28; P < 0.001) were associated with non‐attendance. The difference in gender (88% men vs 70% women; P < 0.001) and age (43 vs 34 years) persisted in the non‐white group. Regression analysis showed that higher baseline HbA1c level (odds ratio 1.96; P = 0.004), younger age (odds ratio 0.98; P = 0.001) and lower social deprivation (odds ratio 0.52; P = 0.001) was associated with attendance. Conclusion: Socio‐economic status and factors perceived as indicating greater severity of disease (HbA1c ) influence attendance at DAFNE. More work is necessary to understand the demography of non‐attenders to aid future service design and alternative engagement strategies for these groups. What's new?: In a large urban area with good provision of diabetes self‐management education, < 30% of eligible adults have attended this programme. Non‐attenders were more likely to be men, from black and minority ethnic groups, from areas of social deprivation and in the older age group. There were associations between attendance at structured education and young age, female gender and higher HbA1c level.